Psychiatric disorders among older prisoners: a systematic review and comparison study against older people in the community - Di Lorito, Claudio; Völlm, Birgit; Dening, Tom (Taylor & Francis, 2017)
Objectives: Despite emerging evidence that older prisoners experience poor mental health, literature in this area is still limited. In the present systematic review and meta-analysis, we report on the prevalence of psychiatric disorders among older prisoners and compare our findings against community studies on older people. Methods: We searched on Assia, PsycInfo, MedLine, Embase, Web of Science, Google and Gov.uk. We carried out bias assessments, rated studies for quality and ran a heterogeneity test. We meta-analysed prevalence rates of psychiatric disorders through an aggregate weighted mean and calculated Relative Risk and statistical significance against community studies. Sensitivity analyses were further performed. Results: We reviewed nine studies and obtained the following prevalence: “Any psychiatric disorder” 38.4%, depression 28.3%, schizophrenia/psychoses 5.5%, bipolar disorder 4.5%, dementia 3.3%, cognitive impairment 11.8%, personality disorder 22.9%, alcohol abuse 15.9%, anxiety disorders 14.2%, PTSD 6.2%. Older prisoners were found to have higher RR for every single psychiatric disorder against older people in the community, with the sole exception of alcohol abuse (RR=1) and dementia (RR=.75). The prevalence rates were statistically significantly higher (p<.05) among the prisoners for “Any psychiatric disorder”, depression and personality disorder. Overall, the sensitivity analyses confirmed our original results. Conclusion: Our findings point at a high prevalence of every single psychiatric disorder among older prisoners, who also experience rates of dementia and alcohol abuse comparable to those reported in the community. Our results have relevant implications for policy and practice in this area. Further research is crucial to confirm findings from this study.